Perancangan Perbaikan untuk Mengurangi Cacat Produk pada Departemen Fiber PT XYZ dengan Metode FTA - Soejanto, Jessica Clarissa; Ekawati, Yurida; Purnomo, Purnomo (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2023)
The fiber department is one of the departments in the PT XYZ produces bus panels and appliances. Based on the fiber production data on August 1 - September 23, 2022, there are 92 defects out of 547 products. It is important to analyze the root cause of the failure in the production process. There are seven types of defects in the manufacturing process that is, fiber is too thick or thin, the fiber surface is rough, fiber has white spots, fiber needs a long time to dry, fiber rejects (liquid/burn), the putty result is imperfect, and the paint is imperfect. The root cause analysis was conducted using Fault Tree Analysis (FTA) method. Based on FTA, defective products can be caused by human, machine, or equipment factors. From that, it will be used for improvement recommendations to improve the quality. Examples of the corrective recommendations are periodic drain engine water, emptying water form, products-checkout form, and roll-cleaning form, using a measuring cup for the catalyst, and a new container for acetone.